Effect of HCG injection on poor fertile rabbits - Yamani K.A.O.; Marai I.F.M.; El Gaafary M.N.; El Kelawy H.M.E. (Rabbit production in hot climates, 1994)
Twenty-six low receptive does and 12 bucks with poor fertility of New Zealand White (NZW) breed were used. The aim was to study the effect of injection of 50 I.U. human chorionic gonodotrophin (HCG; Pregnyl) on productive and reproductive performance of such rabbits. The hormonally treated does were significantly (P less than 0.01 or 0.05) higher than the control in reponse to coitus, conception rate, litter size at birth and bunny weight. However, no significant differences were detected in gestation length, litter weight, litter weight gain and pre-weaning mortality rate between the two experimental groups. Injection intramuscularly with 50 I.U. HCG to bucks with low semen quality increased (P less than 0.01 or 0.05) the ejeculate volume, sperm motility and sperm concentration and decreased (P less than 0.05) the dead and abnormal spermatozoa.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)